2017
DOI: 10.1002/ange.201706764
|View full text |Cite
|
Sign up to set email alerts
|

Colossal Stability of Gas‐Phase Trianions: Super‐Pnictogens

Abstract: Multiply charged negative ions are ubiquitous in nature.T hey are stable as crystals because of charge compensating cations;w hile in solutions,s olvent molecules protect them. However,they are rarely stable in the gas phase because of strong electrostatic repulsion between the extra electrons. Therefore,u nderstanding their stability without the influence of the environment has been of great interest to scientists for decades.While muchofthe past work has focused on dianions, work on triply charged negative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…25 The exchange-correlation energy functional and basis sets used in this paper have been proven to be capable of providing reliable results in previous works. 6,10,11 Moreover, some theoretical results have been validated by experimental study. 9,13,14 Dispersive interactions are considered in all calculations using the D3 version of Grimme's dispersion with the original D3 damping function.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…25 The exchange-correlation energy functional and basis sets used in this paper have been proven to be capable of providing reliable results in previous works. 6,10,11 Moreover, some theoretical results have been validated by experimental study. 9,13,14 Dispersive interactions are considered in all calculations using the D3 version of Grimme's dispersion with the original D3 damping function.…”
Section: Methodsmentioning
confidence: 93%
“…The extraordinary stability of B 12 (CN) 12 2À has been recently experimentally confirmed by Mayer et al 9 and the measured second electron affinity of 5.5 eV is in good agreement with the calculated value. Zhao et al 10 then showed that stable gas-phase tri-anions can be formed by tailoring the composition of the boron core of the dianion. They predicted a stable gas-phase tri-anion, BeB 11 (CN) 12 3À , whose third electron is bound by an extraordinarily large value of 2.65 eV.…”
mentioning
confidence: 99%